Pusat Mode Di Kota Pekanbaru Dengan Penerapan Prinsip Desain Y.B. Mangunwijaya - M. Hadid Qosim; Mira Dharma Susilawaty; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Fashion is a style of dress that is used every day, both in daily life or during certain events with the aim to support the appearance. Fashion education and training spearhead the fashion world. Pekanbaru City does not yet have a place or place to carry out fashion training such as modeling training, fashion warfare training, and cosmetology training which will produce talented generation so that they can perform optimally in local, national and international events. The fashion center can be one right solution to advance the development of fashion in the city of Pekanbaru. This building was planned using the Design Principles of Y. B. Mangunwijaya, known as one of the local architects who used the concept of use and image so that it was very suitable for designing the fashion center in Pekanbaru City.Keywords: Fashion, Y. B. Mangunwijaya, Concept